Responses of respiration in the light to warming in field-grown trees a comparison of the thermal sensitivity of the Kok and Laisk methods - Way, Danielle A (The New phytologist, 2019)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.